Structural, morphological, Raman, dielectric and electrical properties of La1−2xBaxBixFeO3 (0.00 ≤ x ≤ 0.20) compounds. Issue 57 (10th November 2021) - Benali, E. M.; Benali, A.; Bejar, M.; Dhahri, E.; Graca, M. P. F.; Valente, M. A.; Costa, B. F. O.
Abstract : La1−2 x Ba x Bi x FeO3 (0.00 ≤ x ≤ 0.20) nanoparticles were prepared by the auto-combustion method using glycine as a combustion fuel. Abstract : La1−2 x Ba x Bi x FeO3 (0.00 ≤ x ≤ 0.20) nanoparticles were prepared by the auto-combustion method using glycine as a combustion fuel. X-ray diffractometry (XRD) measurements confirmed the orthorhombic structure of the synthesized compounds with the Pnma space group as a principal majority phase and showed the presence of a very minor secondary phase when x > 0.1. The nanosize criterion of the prepared compounds was confirmed from the crystallite size values calculated using the Williamson–Hall formalism. The relaxation process has been studied by the frequency dependence of the imaginary parts of impedance and modulus ( Z ′′ and M ′′) which satisfied the Arrhenius law. Nyquist plots allowed us to obtain an adequate equivalent circuit involving the grains and grain boundary contributions. The activation energies calculated from Z ′′, M ′′ and the resistance of both contributions deduced from the Nyquist plots are found to be very similar. The conduction mechanism has been analyzed using the temperature dependence of the exponent Jonscher's power law parameter which confirms the NSPT conduction mechanism type for all compounds with an enhancement of the binding energy of the charge carrier ( W H ) with the substitution.